Encyclopedia of Family Studies 2016
DOI: 10.1002/9781119085621.wbefs289
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion, Marital

Abstract: Marital cohesion refers to the degree of connectedness, togetherness, and emotional bonding between marital partners. Cohesion in marriages is related to positive relationship qualities, including greater relationship satisfaction and lower hostility between partners. Also, marital cohesion is positively related to individual well‐being, such as higher levels of self‐esteem. Yet, extremely high levels of cohesion may be unhealthy for marriages, reflecting too much dependence between partners. An optimal level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Dyadic bonding in romantic relationships facilitates physical maintenance and emotional proximity with each intimate partner (Mosko & Pistole, 2010). Doohan et al (2009) found couple bonding to be positively linked with intimate partner consensus, which has been demonstrated as integral to relationship quality (Doane, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dyadic bonding in romantic relationships facilitates physical maintenance and emotional proximity with each intimate partner (Mosko & Pistole, 2010). Doohan et al (2009) found couple bonding to be positively linked with intimate partner consensus, which has been demonstrated as integral to relationship quality (Doane, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%